Examining the differences in perceived legal and non-legal factors between drink driving and drug driving - Truelove, Verity (Journal of criminology, 2023)
Drink and drug driving countermeasures have several similarities, yet also have a number of differences. To improve the effectiveness of these countermeasures, it is important to delineate the perceptions of both legal and non-legal factors between drink driving and drug driving. This study aimed to understand these differences and how legal and non-legal factors uniquely contribute to future intentions to engage in these illegal behaviours. A total of 546 licensed drivers who have a history of using both alcohol and drugs (marijuana, MDMA, and/or ice/speed) responded to an online survey that included legal deterrence measures as well as established measures of non-legal factors for both drink driving and drug driving. The non-legal factors included the fear of physical loss (e.g., fear of injuring yourself or others), social loss (e.g., social disapproval) and internal loss (e.g., guilt). Participants were more likely to report drug driving compared to drink driving, with a higher perceived chance of being caught for drink driving and more experience avoiding punishment for drug driving. Physical loss to others and internal loss were higher for drink driving. For both models, punishment avoidance was a significant predictor. Certainty of apprehension and severity punishment were only significant deterrents for drug driving, not drink driving. The threat of physical loss to oneself was a significant deterrent for drink driving, not drug driving. The results show that legal and non-legal deterrents are rated as lower for drug driving compared to drink driving, yet legal sanctions are still a deterrent for drug driving. Further, non-legal countermeasures are needed for both drink and drug driving that increase drivers? perceived fear of physical loss to others, internal loss, and social sanctions associated with the behaviours.